EVALUASI PENGGUNAAN OBAT TRADISIONAL BERDASARKAN DIMENSI KETEPATAN CARA PENGGUNAAN - Rahmasiah; Shabran Hadiq; Washliaty Sirajuddin (Jurnal Farmasi IKIFA, 2024)
This research aims to evaluate the use of traditional medicine in Lautang Benteng Village, Sidenreng Rappang Regency. The research was carried out from 09 August 2022 to 09 September 2022 in Lautang Benteng Village, Maritengngae District, Sidenreng Rappang Regency. The type of research used in this research is the Quantitative Method, while the sampling technique in this research uses purposive sampling where the number of respondents used is 25 respondents, namely the people of Lautang Benteng Village who have met the criteria. Primary data in this research was obtained by distributing questionnaires to respondents while being given instructions for filling in to avoid errors in filling in the questionnaire. What was done next was Data Entry, Data Management, then Analysis. The criteria for respondents are divided into several characteristics, namely based on gender, consisting of 9 men with a percentage of 36% and 16 women with a percentage of 64%. Characteristics based on age, aged 12-25 years are 9 people with a percentage of 36 %, those aged 26-45 years were 6 people with a percentage of 24%, and those aged 46 years and over were 10 people with a percentage of 40%. Based on the research results in accordance with the problem formulation, it can be concluded that the evaluation of the use of traditional medicines by the community is based on dimensions The accuracy of using traditional medicines is 76%.